(untitled) (Eurasian Journal of Ecology, 2019)
The article presents the results of research of the radioecological situation in Kalachi village of Akmola region due to sleepy sickness. No radioactive contamination was detected in the territory of Kalachi village. Established levels of external dose from natural gamma radiation are on average 0.2 μSv/h. In the environment (drinking water and surface watercourses) of Kalachi, the content of man-made radionuclides has not been detected, or it is at the level of the background of global precipitation. Content of natural radionuclides is typical for the Republic of Kazakhstan. However, studies of basement premises revealed an excess of radon concentration of 3-6 times compared to the standards. Key words: radon, gamma radiation, dosimetry, radionuclides, sleeping sickness